Hes1 in malignant tumors: from molecular mechanism to therapeutic potential - Zhang, Liping; Zhang, Qian; Guo, Cheng; Ru, Zixin; Yang, Zetian; Geng, Yi; Yang, Junjie; Zhang, Daigui; Yang, Zhenhuai; Huang, Shuicai (Frontiers in Immunology, 2025)
The occurrence and development of malignant tumors involve abnormalities in complex molecular regulatory networks, among which the abnormal activation of the transcriptional regulator hairy and enhancer of split 1 (Hes1) has attracted significant attention in recent years and is closely associated with prognosis in various malignancies. Hes1 exhibits high expression in various solid tumors and hematological malignancies, where it participates in alterations involving diverse immune cells, inflammatory factors, and the immune microenvironment, thereby promoting tumor cell proliferation, invasion, metastasis, and resistance to treatment. Recent studies have widely investigated the potential of targeting Hes1 and inhibiting its expression as a cancer therapeutic strategy, although its precise mechanisms of action are not yet fully elucidated. Hes1 interacts with critical pathways including Notch, JAK/STAT, PI3K/AKT/mTOR, and Wnt/β-catenin. These interactions form complex crosstalk networks that drive malignant transformation and progression. Furthermore, Hes1 plays a central role in the formation of an immunosuppressive tumor microenvironment (TME) and immune escape by regulating the expression of immune checkpoint-associated proteins, extracellular matrix (ECM) remodeling, and other processes, making it a highly promising therapeutic target. Notably, the expression level of Hes1 is significantly correlated with tumor clinical stage, prognosis, and drug resistance. This review comprehensively introduces the mechanisms of Hes1 in the progression of malignant tumors, with a particular focus on discussing its application and underlying mechanisms in tumor immunotherapy. It integrates the latest clinical evidence and preclinical research perspectives. The goal is to highlight the translational potential of Hes1 as a novel biomarker and molecular target.